Legal Liability for Online Purchase Agreements for Used Smartphones That Experience Damage - Alvina Hardiyanti Ritonga; Desi Ira Ari Fitri; Gustina Tri Lestari Putri; Qania Athaya Fakira; Rida Arantika (Jurnal Sahabat ISNU SU, 2025)
Advances in digital technology have impacted online buying and selling transactions, including the trade of used smartphones. These transactions often face challenges, particularly the risk of damaged goods that buyers only discover after receiving them. This study analyzes legal liability in online used smartphone sales agreements and consumer protection under Indonesian law. Using a normative juridical method, this study examines the Civil Code (KUH Perdata), Law Number 8 of 1999 concerning Consumer Protection, and other regulations. The results indicate that sellers are required to provide honest information about the condition of goods, buyers are responsible for understanding descriptions and policies, and digital platforms play a role in providing protection through escrow systems and return policies. A gap between regulation and practice was identified, necessitating legal reform to improve consumer protection. This research is expected to encourage transparent and secure e-commerce.